Coclosed Rickart Modules - Ahmed, Ghaleb; Ahmed, Ghaleb (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2018)
Let  be a right module over an arbitrary ring  with identity and  . In this work, the coclosed rickart modules as a generalization of  rickart  modules is given. We say  a module  over   coclosed rickart if for each ,   is a coclosed submodule of  . Basic results over this paper are introduced and connections between these modules and otherwise notions are investigated.